2017
DOI: 10.20944/preprints201709.0131.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimators and Confidence Intervals for Plant Area Density at Voxel Scale with T-LiDAR

Abstract: 9Terrestrial LiDAR becomes more and more popular to estimate leaf and plant area density. 10Voxel-based approaches account for this vegetation heterogeneity and significant work has 11 been done in this recent research field, but no general theoretical analysis is available. 2• Our unbiased estimators are consistent in a wider range of validity than the usual ones, 26 especially for the unbiased MLE, which is consistent when the beam number is as low as 5. 27The unbiased MLE is efficient, meaning it reaches t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…These results indicate that leaf area density is increasingly overestimated when total path length is relatively short, as predicted by Pimont et al. (2018). From this figure, one can see a sharp increase in the mean bias and the standard deviation in leaf area density estimates (centre curve in Figure 2) which occurs on average across all sites around 30 m of total probe length.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…These results indicate that leaf area density is increasingly overestimated when total path length is relatively short, as predicted by Pimont et al. (2018). From this figure, one can see a sharp increase in the mean bias and the standard deviation in leaf area density estimates (centre curve in Figure 2) which occurs on average across all sites around 30 m of total probe length.…”
Section: Resultssupporting
confidence: 82%
“…Terrestrial laser scanning (TLS) has been shown to enable the mapping of leaf area density in forests (Béland et al., 2011, 2014; Grau et al., 2017; Hosoi & Omasa, 2006; Pimont et al., 2018). The use of observations from terrestrial laser scanners provides two fundamental advantages over traditional passive methods for deriving leaf area density in forests: (a) the elements intercepting laser light are positioned in 3D space, and (b) the intensity of the returned light is measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume occupied by vegetation within each transect was divided into 1 m 3 voxels, and the PAD calculated for each of these voxels (Supplementary Figure 1d). This procedure was done in the LiDAR data voxelization software AMAPVox 48,49 . AMAPvox tracks every laser pulse through a 3D grid (voxelized space) to the last recorded hit.…”
Section: Terrestrial Laser Scanning: Data Acquisition Registration and Plant Area Index Estimationmentioning
confidence: 99%
“…Different estimation procedures are provid ed in the AMAPVox software. We used the Free Path Length estimator first developed for single return TLS in Pimont and colleagues 49 and later extended to the multiple return case 50 . The common assumption made for all estimation procedures in AMAPvox is to consider vegetation elements as randomly distributed within a voxel (thereby neglecting within voxel clumping) and to express the directional gap probability (or directional transmittance) as a function of the optical path length of laser pulse through a voxel and the local extinction coefficient 51 .…”
Section: Terrestrial Laser Scanning: Data Acquisition Registration and Plant Area Index Estimationmentioning
confidence: 99%